QoE-Driven Energy-Aware Multipath Content Delivery Approach for MPTCP-Based Mobile Phones - Yuanlong Cao Shengyang Chen Qinghua Liu Yi Zuo Hao Wang Minghe Huang (中国通信（英文版）, 2017)
Mobile phones equipped with multiple wireless interfaces can increase their goodput performance by making use of concurrent transmissions over multiple paths, enabled by the Multipath TCP （MPTCP）. However, utilizing MPTCP for data delivery may generally result in higher energy consumption, while the battery power of a mobile phone is limited. Thus, how to optimize the energy usage becomes very crucial and urgent. In this paper, we propose MPTCP-QE, a nov- el quality of experience （QoE）-driven energy-aware multipath content delivery approach for MPTCP-based mobile phones. The main idea of MPTCP-QE is described as follows： it first provides an application rate-aware energy-efficient subflow management strategy to tradeoff throughput performance and energy consumption for mobile phones; then uses an available bandwidth-aware congestion window fast recovery strategy to make a sender avoid unnecessary stow-start and utilize wireless resource quickly; and further introduces a novel receiver-driven energy-efficient SACK strategy to help a receiver possible to detect SACK loss timely and trigger loss recovery in a more energy-efficient way. The simulation results show that with the MPTCP-QE, the energy usage is enhanced while the performance level is maintained compared to existing MPTCP solutions.